The effect of problem solving learning model based just in time teaching (JiTT) on science process skills (SPS) on structure and function of plant tissue concept - Resha Maulida; Nengsih Juanengsih; Yuke Mardiati (JPBI (Jurnal Pendidikan Biologi Indonesia), 2017)
The purpose of this study was to determine the effect of Problem Solving learning model based Just in Time Teaching (JiTT) on students' science process skills (SPS) on structure and function of plant tissue concept. This research was conducted at State Senior High School  in South Tangerang .The research conducted using the quasi-experimental with Nonequivalent pretest-Postest Control Group Design. The samples of this study were 34 students for experimental group and 34 students for the control group. Data was obtained using a process skill test instrument (essai type) that has been tested for its validity and reliability. Result of data analysis by ANACOVA, show that there were significant difference of postest between experiment and control group, by controlling the pretest score (F = 4.958; p <0.05). Thus, the problem-solving learning based on JiTT proved to improve students’ SPS. The contribution of this treatment in improving the students’ SPS was 7.2%. This shows that there was effect of problem solving model based JiTT on students’ SPS on the Structure and function of plant tissue concept.